2019
DOI: 10.26905/afr.v2i2.3729
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi, Pengetahuan Akuntansi dan Pengalaman Usaha Terhadap Penggunaan Informasi Pada UMKM

Abstract: The purpose of this research was to determine the effect of perceptions and accounting knowledge on the use of accounting information. This research adds a moderating variable that is to strengthen the relationship between perception, accounting knowledge on the use of accounting information. The data obtained are primary data sourced from questionnaires and direct interviews with MSMEs and the analysis technique used is multiple regression analysis. The results of this research indicate that the moderating va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results of the study showed that educational background p = 0.004 and accounting knowledge variable p = 0.001, which means that each independent variable affects the dependent variable (Astuti et al, 2023). The study results show that accounting knowledge affects the use of accounting information, and business experience does not affect the use of accounting information (Pamungkas & Kristianti, 2019). The study results show that educational background does not affect the use of accounting information, accounting knowledge has a positive effect on the use of accounting information, and entrepreneurial spirit has a positive effect on the use of accounting information (Kaukab et al, 2020).…”
Section: Introductionmentioning
confidence: 80%
“…The results of the study showed that educational background p = 0.004 and accounting knowledge variable p = 0.001, which means that each independent variable affects the dependent variable (Astuti et al, 2023). The study results show that accounting knowledge affects the use of accounting information, and business experience does not affect the use of accounting information (Pamungkas & Kristianti, 2019). The study results show that educational background does not affect the use of accounting information, accounting knowledge has a positive effect on the use of accounting information, and entrepreneurial spirit has a positive effect on the use of accounting information (Kaukab et al, 2020).…”
Section: Introductionmentioning
confidence: 80%
“…Students represent the future leaders and the next generation of the nation (Utami & Nanda, 2019;Zhafira et al, 2020). Therefore, it is crucial for students to possess positive knowledge and attitudes towards the green accounting concept (Erwinsyah, 2021;Pamungkas & Kristianti, 2019). Human attitudes are a primary factor in predicting daily actions, although other factors such as the environment and individual beliefs also play roles.…”
Section: Introductionmentioning
confidence: 99%
“…Students' perceptions of green accounting can be understood through the theory of perception, which highlights how individuals perceive information, benefits, and impacts of green accounting practices in the context of a green economy (Hatane et al, 2020;Pamungkas & Kristianti, 2019). Meanwhile, perception is a stage in the process of interpreting stimuli received by the senses and transforming it into understanding (Zhafira et al, 2020) In the evolution of accounting, there have been periods where the focus drifted away from social and environmental aspects.…”
Section: Introductionmentioning
confidence: 99%